Digital Simulation Model for a Counter Flow Desiccator System - Dogra, A K; Panwar, J S (Journal of Agricultural Engineering, 2001)
A digital simulation model for a counter flow liquid desiccator system was developed and evaluated for dehumidification of air. The humidities at the desiccator outlet were predicted and compared with the observed values. The rate of moisture absorption from the air in the desiccator column was greatly influenced by the airflow rate (95-124 kg/hr) and the ambient conditions at the desiccator inlet. The Maximum moisture absorption rate of 0.21 kg/h was observed at 124.65 kg/h airflow rate and ambient air temperature of 26.5Â°C.